THE PHILOSOPHY OF MORALITY: UKRAINIAN PERSPECTIVE - Volodymyr Kafarskyi (Vasyl Stefanyk Precarpathian National University, 2015)
The article deals with the problems of historiosophy, whose subject matter is human and social world view, its historical, religious, intellectual, ethical and aesthetical aspects. Hence historiographical interpretation of the concept of morality, ethical criteria, and distinction between morality and ethics. These issues are viewed from the perspective of spiritual morality. Assuming that spiritual values affect deepest human feelings, our life principles and attitude to God in a special way , morality may be defined as the system of interrelationship among people, which comprises spiritual values, life experience, ways and traditions. Such an approach helps to comprehend the degree to which spiritual values influence morality and religious views of the Ukrainian people, the specific way in which the system of ethical values was built in the time of the Messianic Christianity. The formation of world view, morality and ethics is closely related to the issues of faith and social life, as well as to the development of the national philosophy and theology, both in the past and nowadays; these processes and phenomena are a significant factor in the way Ukrainians perceive themselves, the world around them and the Universe.